Sex with kings 500 years of adultery, power, rivalry, and revenge - Herman, Eleanor (Morrow, 2004)
Chronicles five hundred years of adultery in European monarchy, discussing how royal mistresses influenced every aspect of European history, and profiling notable women and the kings who loved them.